fractional differential equations with intial conditions at inner points - beggat, roufeida; beggat, aicha (universty of elouedجامعة الوادي, 2021)
قمنا في هذه المذكرة بدراسة المعادلات التفاضليّة الكسرية ذات الشروط الإبتدائية الداخلية، بشكل أدق حاولنا عرض إثبات نظرية بيانو، وذلك باستعمال مشتق كابيتو ونظرية النقطة الثابتة.In this dissertation we study the existence and uniqueness of the initial value problem for nonlinear fractional differential equations with initial conditions at inner points. More precisely, we will prove a Peano type theorem of the fractional version, with using Caputo derivative and fixed point theorems.
mémoier master mathématique
Keywords: المشتقات الكسرية، معادلات تفاضلية، مسألة قيمة إبتدائية، نظرية النقطة الثابثة، معادلات تفاضلية الكسرية الاعتيادية.; Fractional Derivative, Differential Equation, Initial Value Problem, Fixed Point Theorem, Ordinary Fractional Differential Equation.